'If you feel that nobody wants you you'll withdraw into your own': Gypsies/Travellers, networks and healthcare utilisation. Issue 8 (10th April 2013) - Smith, David; Ruston, Annmarie
Abstract Gypsies and Travellers are the unhealthiest group in British society, suffering from higher levels of physical and mental illness, lower life expectancy and with low levels of healthcare utilisation. They also continue to experience the highest level of prejudice and discrimination in society. While studies indicate that social networks play an important role in shaping health beliefs and the response to symptoms, evidence on the influence of networks on health is unclear and contradictory. This article draws on social network theory and research into the relation between discrimination and health to critically examine how networks mediate between collective experiences of racism and health‐related behavior. Qualitative interviews with 39 adult Gypsies and Travellers were conducted in the South‐East of England to explore the wider structural and institutional context and the influence those contexts play in shaping health beliefs and decisions whether to access formal health services. The findings indicate that the influence networks play in shaping health behaviour is dependent on the particular social context of the group and its status in relation to wider social structures, making generalization problematic.